Evoluç\~ao da produtividade total dos fatores da indústria brasileira considerando a obsolescência do capital instalado (1990-2009) - Luiz Dias Bahia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This article tries to calculate the total factor productivity (TFP) of the Brazilian supply chains and also the obsolescence of their capital between 1990 and 2009. We conclude two main aspects about our investigation: firstly, liquid obsolescence TFP have grown strongly after 1995, but not after 1990; secondly, it is right to conclude that have been a expressive technological improvement of the Brazilian supply chains after 1995.
Keywords: D2; L6; D91; 330; Brazilian manufacturing; productivity; capital